Enhanced Sensing Sensitivity of Long Period Fiber Grating by Self-Assembled Polyelectrolyte Multilayers - Ng, Foong Mun (2015)
Coating technique is one of the common methods used to enhance the sensing capability on Long Period Fiber Grating (LPFG) fiber sensor. The main drawback of coating technique like layer by layer (LBL) is time consuming for establishing the layer by layer coating on fiber sensor. It showed that the optimal sucrose sensitivity can be improved by 20 to 25% when applying 100 bilayers of poly(allylamine hydrochloride) (PAH)/poly(sodium-p-styrenesulfonate) (PSS) coating on LPFG by Qiushun Li et al. In this project, we proposed a new method to reduce the number of bilayers using double-pass configuration which has showed significant improved in terms of power referenced sensing. The coating materials was done by using positive charged PDDA (poly-diallyldimethylammonium chloride) and negative charged PSS (poly-sodium styrene suffocate) to form the multiple layers coating on the LPFG. The sensitivity performance was verified by the various concentration of sucrose solutions. From the experiment result, it showed that the increment of concentration of sucrose solution caused the LPFG transmission spectra gradually moving toward the short wavelength side. The comparison of single pass LBL and double pass LBL indicated that significant improvement of sucrose sensing in terms of power referenced for double pass as compared to single pass with LBL at certain range of sucrose concentration. In conclusion, it is achievable to reduce the number of coating layers using double pass to get comparable sucrose sensitivity sensing result.